Tinjauan Yuridis Pemberian Bantuan Hukum Bagi Pekerja Migran Indonesia Di Negara Penempatan (RechtJiva, 2025)
Obtaining legal assistance when Indonesian migrant workers face legal problems is one of their fundamental rights during employment. This right is stipulated in Article 21 paragraph (1) letter (f) of the Law on the Protection of Indonesian Migrant Workers. However, this provision is not accompanied by further regulations governing the implementation of legal aid as referred to in Article 21 paragraph (1) letter (f) of the same law. This condition results in a legal gap, causing many Indonesian migrant workers to face legal problems abroad without adequate legal assistance. This study employs a normative legal research method using statutory, conceptual, and comparative approaches. It utilizes primary, secondary, and tertiary sources of legal materials. All legal materials were analyzed using the legal construction method through systematic interpretation. The findings of this study reveal the urgency of the issue, as many Indonesian migrant workers still lack sufficient legal representation. Moreover, the existing data indicate a significant annual increase in the number of migrant worker placements. The absence of comprehensive legal provisions governing legal aid for Indonesian migrant workers facing legal issues abroad contradicts Article 28D paragraphs (1) and (2) of the 1945 Constitution of the Republic of Indonesia. To ensure effective protection for Indonesian migrant workers in such situations, it is necessary to establish specific regulations addressing aspects such as the funding of legal aid for migrant workers, inter-agency cooperation and division of authority, eligibility criteria for legal aid recipients, and the types of legal assistance provided.